Efektivitas Fly Ash Sebagai Adsorben Dalam Menurunkan Chemical Oxygen Demand (COD) pada Air Limbah Pulp and Paper - Nurjanah, Irma; Jalius, Jalius; Viareco, Hariestya (Jurnal Pelita Teknologi, 2023)
This study aims to determine the characteristics of fly ash as an adsorbent that has been activated and to determine the optimum conditions of fly ash adsorbent to reduce the COD value of pulp and paper wastewater. The characteristics of water content, ash and iodine number were tested. The quality of fly ash adsorbent is done by determining the optimum pH, mass and time. The variations of pH 4,5,6,7,8,9 and 10, mass 0.5 g, 1 g, 1.5 g, and 2 g and contact time variations are 5 minutes, 15 minutes, 30 minutes, 45 minutes and 60 minutes. This research method uses experimental method with Complete Randomized Design analysis by conducting Anova test and Duncan's further test.  The results showed that the test results of the characteristics of water content, ash and iodine number have met SNI 06-3730-1995 regarding technical activated charcoal. The optimum conditions obtained during adsorption consisting of optimum pH was found at pH 4 with % Removal COD as much as 18.1%, the optimum mass obtained was 1 gram with % Removal COD as much as 24.8%, while the optimum time obtained was 15 minutes with % Removal COD as much as 20.38%. The adsorption results show that the decrease in COD of pulp and paper wastewater is still not effective in accordance with PermenLH No. 5 of 2014.